Calcium Signaling Regulated by Cellular Membrane Systems and Calcium Homeostasis Perturbed in Alzheimer’s Disease - Huang, Dong-Xu; Yu, Xin; Yu, Wen-Jun; Zhang, Xin-Min; Liu, Chang; Liu, Hong-Ping; Sun, Yue; Jiang, Zi-Ping (Frontiers in Cell and Developmental Biology, 2022)
Although anything that changes spatiotemporally could be a signal, cells, particularly neurons, precisely manipulate calcium ion (Ca2+) to transmit information. Ca2+ homeostasis is indispensable for neuronal functions and survival. The cytosolic Ca2+ concentration ([Ca2+]CYT) is regulated by channels, pumps, and exchangers on cellular membrane systems. Under physiological conditions, both endoplasmic reticulum (ER) and mitochondria function as intracellular Ca2+ buffers. Furthermore, efficient and effective Ca2+ flux is observed at the ER-mitochondria membrane contact site (ERMCS), an intracellular membrane juxtaposition, where Ca2+ is released from the ER followed by mitochondrial Ca2+ uptake in sequence. Hence, the ER intraluminal Ca2+ concentration ([Ca2+]ER), the mitochondrial matrix Ca2+ concentration ([Ca2+]MT), and the [Ca2+]CYT are related to each other. Ca2+ signaling dysregulation and Ca2+ dyshomeostasis are associated with Alzheimer’s disease (AD), an irreversible neurodegenerative disease. The present review summarizes the cellular and molecular mechanism underlying Ca2+ signaling regulation and Ca2+ homeostasis maintenance at ER and mitochondria levels, focusing on AD. Integrating the amyloid hypothesis and the calcium hypothesis of AD may further our understanding of pathogenesis in neurodegeneration, provide therapeutic targets for chronic neurodegenerative disease in the central nervous system.